Analisis Dan Perancangan Data Warehouse Pada PT Gajah Tunggal Prakarsa - Huda, Choirul; Pangestu, Bram; Lai, Jimmy; Teja, Riantoro (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this helpful in making decisions more quickly and precisely. Research methodology includes analysis study was to analyze the data base support in helping decisions making, identifying needs and designing a data warehouse. With the support of data warehouse, company leaders can be more of current systems, library research, designing a data warehouse using star schema. The result of this research is the availability of a data warehouse that can generate information quickly and precisely, thus helping the company in making decisions. The conclusion of this research is the application of data warehouse can be a media aide related parties on PT. Gajah Tunggal initiative in decision making.